Investigation and characterization of Stellite-based wear-resistant coatings applied to steel moulds by cold-spray. Issue 1 (2015) - Lucchetta, G.; Giusti, R.; Vezzù, S.; Bariani, P.F.
Abstract: The potential of the cold-spray process in depositing Stellite coatings on annealed steel was explored in the manufacture of wear-resistant injection moulds. Aspects related to both the deposition process and the topography, such as roughness, chemical composition, hardness and wear resistance were investigated. Stellite 6, Stellite 31 and Stellite 31 + 10% AISI 316L coatings were deposited and the effects of composition were analyzed to identify the optimum process conditions. The performance of the coated samples was evaluated through a specially developed compression test. Cold-spray deposition of Stellite coatings proved to be a valid alternative to heat treatment in manufacturing wear-resistant moulds.